Corrosion analysis of internal surface of carbon steel natural gas piping - Mohd Fuad , Ibrahim (2013)
Oil and gas industry has been contributing as a largest government income and this industry manage to control corrosion which causing wear failure in gas pipelines and potentially cause substantial human and economic losses. The objective of this study is to study the effect of H2S04 solution concentration electrolyte to corrosion behaviour of the internal surface of natural gas pipeline by using Tafel Extrapolation Method. This research starts with sample preparation where the sample from gas pipelines has taken and cut into 1 Omm x 20 mm dimension. This sample has been tested in corrosion test experiment to collecting and analysing the data gain from Tafel slope analysis, Optical Microscopy (OM) and Scanning Electron Microscopy (SEM) to perform corrosion rate and it effect on the surface morphology and microstructure. Due to the result of this study, it is point out that corrosion rate increase with high concentration of H2S04 which presence in natural gas composition. The data can be used to managing the pipelines effectively and prevention method can be taken in order to extend the life span of the pipeline.